1973
DOI: 10.1139/v73-193
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ozonolysis. The Initial Ozonide. Lack of Evidence for "Unified Concept" Involving Staudinger Molozonide

Abstract: Contrary to previous reports cyclohexanone and pinacolone are not oxidized to the corresponding Baeyer–Villiger oxidation products during ozonolysis of ethylidenecyclohexane in their presence. Addition of propionaldehyde to a solution of the 1,2,3-trioxolane initial ozonide of trans-1,2-di-t-butylethylene resulted in oxidation of the aldehyde to propionic acid and reduction of the 1,2,3-trioxolane to pivaldehyde. Thus, there is no necessity for the four-membered Staudinger molozonide as an ozonolysis intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Specifically, 8 reportedly was formed in high yield from ethylidenecyclohexane. However, no 8 could be detected among the products when the reaction was repeated (13,44). Also, the reported synthesis, using this reaction, of the dioxetane of bifluorenylidene (45) could not be repeated in two laboratories (36h 46).…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, 8 reportedly was formed in high yield from ethylidenecyclohexane. However, no 8 could be detected among the products when the reaction was repeated (13,44). Also, the reported synthesis, using this reaction, of the dioxetane of bifluorenylidene (45) could not be repeated in two laboratories (36h 46).…”
Section: Discussionmentioning
confidence: 97%
“…Story et al22 explain their results by postulating a reductive ozonolysis, that is, a reaction in which aldehyde is oxidized to acid and an ozonolysis intermediate (they suggest the Staudinger23 molozonide) is reduced. Bailey et al 20 have observed a similar effect of added aldehyde on ozonide yield but suggest that the aldehyde is oxidized by some other intermediate, possibly a 1,2,3-trioxolane or carbonyl oxide.…”
mentioning
confidence: 88%